Becoming a coach: experiences of faculty educators learning to coach medical students - Brooks, Joanna Veazey (BMC Med Educ, 2020)
BACKGROUND: Despite the growth of coaching in medical education, many questions remain about the process of becoming a coach for medical students. We sought to understand the process through which faculty acclimated to this new role, and what benefits and challenges they experienced. METHODS: A multi-phase qualitative focus group study was conducted with 20 faculty at one medical school in the United States during the initial year coaching was implemented. Focus group transcripts were analyzed using the constant comparative approach to inductively identify themes from the data. RESULTS: Four main benefits were reported by faculty: student guidance, identifying student issues early, helping students develop work-life balance, and fostering clinician connectivity, which was seen as benefitting both students and faculty. The two main challenges were uncertainty regarding how adaptive the coaching sessions should be, and difficulty engaging in some of the roles simultaneously, like mentoring and supervision. CONCLUSIONS: Schools that develop academic medical student coaching programs should design faculty support around coaching and recognize that the process of becoming a coach may not be or feel straightforward for faculty. Overall, faculty found coaching to be rewarding despite challenges they experienced.